THE POTENTIAL OF MARINE COMPOUNDS IN NEURODEGENERATIVE DISEASE TREATMENT - AZIZOVA, FERUZA; MHSNHASAN , MUNTADER; NASRITDIN UGLI, GIYOSIDDINOV ABDURAKHIM; KUMAR, KRISHNAMURTHY; BHANJA, MR. MRUTYUNJAYA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Clinical trials with the drug candidates that inhibit protein aggregation are in progress. Disease progression can be prevented by use of these drugs. These drug candidates hold the promise to substantially reduce the occurrence of such diseases if given pre-symptomatically Prevalence of neurodegenerative diseases is increasing with increase in the age of the population. Due to their multi systemic nature several challenges have occurred for the potential treatment of neurodegenerative diseases. The existing drug repositioning research on Neurogenerative therapeutics integrated an integrative strategy of a number of computational repositioning approaches. Network-based analysis was conducted to model the complex interactions between biological molecules and pathways to identify probable drug targets for both the diseases of our concern. Specifically, we constructed protein-protein interaction networks and signalling/regulatory pathways associated with the pathology through a variety of pathway databases and protein-protein interaction resources. By network topology analysis, we found proteins which can potentially function as key intervention points upon perturbation by drug compounds.